Law Enforcement of Criminal Actions for Capital Market Insider Trading Carried Out by Corporations Based on Law Number 8 of 1995 - Mery Rohana Lisbeth Sibarani (Universitas Muhammadiyah Palu, 2024)
Corporations in Indonesia are legal subjects because they have rights and obligations. The capital market has high volatility so that insider trading is very detrimental to the implementation of the capital market which is one of the country's economic instruments. The issue of insider trading as an individual has been regulated in Law Number 8 of 1995, however the implementation of the imposition on corporate criminal sanctions has not yet been rigidly regulated or applied. This research aims to determine how criminal sanctions and insider trading regulations are carried out by corporations based on the Capital Markets Law. The method used is normative juridical. The results of this research found that insider trading regulations are located in articles 95 to 99 of the Capital Markets Law and investigation procedures are under BAPEPAM-LK. The crime of corporate insider trading can be punished because of Article 1 point 23 of the Capital Markets Law and the maximum fine is contained in Article 14, namely a fine of IDR 15,000,000,000.00.